A Flexible Aqueous Zinc–Iodine Microbattery with Unprecedented Energy Density. Issue 15 (4th March 2022) - Jin, Xuting; Song, Li; Dai, Chunlong; Xiao, Yukun; Han, Yuyang; Li, Xiangyang; Wang, Ying; Zhang, Jiatao; Zhao, Yang; Zhang, Zhipan; Chen, Nan; Jiang, Lan; et al.
Abstract: Currently, reported aqueous microbatteries (MBs) only show unsatisfactory electrochemical performance (≤120 mWh cm −3 volumetric energy density and <1000 μWh cm −2 areal energy density) and it remains challenging to develop durable aqueous MBs that can simultaneously offer both high volumetric and areal energy density. Herein, an in situ electrodeposition strategy is adopted to construct a flexible aqueous zinc–iodine MB (ZIDMB). Notably, the fabrication process well avoids the use of common additives (such as binders, conductive agents, and toxic solvent) and also bypasses subsequent time‐consuming procedures such as grinding, coating, drying, etc., thus greatly simplifying the manufacture of the ZIDMB. Meanwhile, owing to the suppression of the shuttle effect of triiodide ions and the high ionic conductivity of the polyelectrolyte, the ZIDMB can simultaneously deliver record‐high volumetric and areal energy densities of 1647.3 mWh cm −3 and 2339.1 μWh cm −2, thus achieving values at least 13.5‐ and 2.3‐fold better than those of best available aqueous MBs, respectively. This work affords an innovative strategy to construct an ideal micro‐power‐source for future miniaturized and integrated electronics. Abstract : A flexible aqueous zinc–iodine microbattery with >1500 mWh cm −3 volumetric energy density and >2000 μWh cm −2 areal energy density is developed by a simple and effective strategy where an iodine cathode is generated in situ during charging. This work affords an innovative strategy to construct an ideal micro‐power‐source for future miniaturized and integrated electronics.